Kelayakan Usaha Peternakan Ayam Broiler Di Desa Mekarjaya Kabupaten Tasikmalaya (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
Broiler chicken farming is one of the important agricultural subsectors in the development strategy, meaning that livestock becomes a medium for providing food to meet people's needs for animal protein and becomes a source of sustainable income and improves the biological environment. The aim of this research is to find out how feasible the broiler chicken farming business is in Mekarjaya Sukaraja village, Sukaraja sub-district, Tasikmalaya regency. This research uses quantitative descriptive analysis methods and data collection using interview, observation and questionnaire methods. The research sample used a purposive sampling method or was determined deliberately, the research sample was the owner of the chicken farm, Mr. Rizky. The eligibility criteria for Mr. Rizqy's broiler chicken farming business are obtaining a Net Present Value (NPV) of IDR. 84,834,320. Internal Rate of Return (IRR) is 20%, Payback Period (PP) is 3.86 years and Net B/C is IDR. 1.7. All business feasibility criteria show that a chicken farming business is feasible to run. If Mr. Rizqy wants to start the business again the following year with capital of Rp. 150,000,000 broiler chicken farming business could be one option.